Effectiveness of coconut water (Cocos nucifera) in feed on masculinization and growth factors of nile tilapia (Oreochromis niloticus) - Sukmawati; Kalesaran, Ockstan J.; Warouw, Veibe; Mokolensang, Jeffrie F.; Paransa, Darus Sa'adah Johanis; Salaki, Christina Leta (AQUATIC SCIENCE & MANAGEMENT, 2025)
This study evaluated the effectiveness of coconut water (Cocos nucifera) applied as a spray onto feed for the masculinization and growth performance of Nile tilapia (Oreochromis niloticus). The 63-day experiment employed a completely randomized design (CRD) with five treatments of coconut water doses (0, 0.10, 0.15, 0.20, and 0.25 mL/g feed) and three replications. Measured parameters included male proportion, growth performance (absolute length and weight, specific growth rate), survival rate, and water quality. Results indicated that coconut water supplementation significantly influenced masculinization and growth. The optimal dose was 0.15 mL/g feed, which yielded the highest male proportion (63.65%)—a 13.65% increase over the control. At this dose, absolute length and weight reached 7.15 cm and 5.34 g, respectively, with a specific growth rate of 8.62%. In contrast, higher doses (0.20-0.25 mL/g) reduced both masculinization and growth performance, despite high survival rates (90-95%). Water quality parameters remained within optimal ranges throughout the trial. These findings suggest that coconut water is a viable, eco-friendly alternative to synthetic hormones for tilapia masculinization and can enhance growth when applied at the recommended dosage.